Delayed intraventricular hemorrhage with hydrocephalus following evacuation of post traumatic acute subdural hematoma - Kumar, Raj; Kalra, Samir Kumar; Das, Rupant Kumar; Vaid, Vivek Kumar; Mahapatra, Ashok Kumar (Indian Journal of Neurotrauma, 2007)
The incidence of intraventricular hemorrhage (IVH) has been increasing recently due to increased detection. The occurrence following evacuation of an acute subdural hematoma (SDH) is extremely rare. The exact mechanism of traumatic IVH in these cases has not been well documented; the erosion of the ventricular wall by adjacent hematoma has been described as the most plausible cause. The rupture of unsuspected vascular malformation following head injury has also been suggested.A case with a delayed IVH following evacuation of acute SDH is reported and the underlying pathophysiology is discussed. This entity needs to recognized and kept in mind as a potential cause of post surgical deterioration in such patients.
Keywords: intraventricular hemorrhage; head injury